Voices from the Ancestors : Xicanx and Latinx Spiritual Expressions and Healing Practices - Gonzalez, Martha R. (Book collections on Project MUSE., 2019)
Voices from the Ancestors brings together the reflective writings and spiritual practices of Xicanx, Latinx, and Afro-Latinx womxn and male allies in the United States who seek to heal from the historical traumas of colonization by returning to ancestral traditions and knowledge. This wisdom is based on the authors' oral traditions, research, intuitions, and lived experiences--wisdom inspired by, and created from, personal trajectories on the path to spiritual conocimiento, or inner spiritual inquiry. This conocimiento has reemerged over the last fifty years as efforts to decolonize lives, minds, spirits, and bodies have advanced. Yet this knowledge goes back many generations to the time when the ancestors understood their interconnectedness with each other, with nature, and with the sacred cosmic forces--a time when the human body was a microcosm of the universe. Reclaiming and reconstructing spirituality based on non-Western epistemologies is central to the process of decolonization, particularly in these fraught times. The wisdom offered here appears in a variety of forms--in reflective essays, poetry, prayers, specific guidelines for healing practices, communal rituals, and visual art, all meant to address life transitions and how to live holistically and with a spiritual consciousness for the challenges of the twenty-first century.